Genome-Wide Identification and Functional Analysis of Carboxylesterase and Methylesterase Gene Families in Peach (Prunus persica L. Batsch) - Cao, Xiangmei; Duan, Wenyi; Wei, Chunyan; Chen, Kunsong; Grierson, Don; Zhang, Bo (Frontiers in Plant Science, 2019)
Carboxylesterases (CXE) and methylesterases (MES) are hydrolytic enzymes that act on carboxylic esters and are involved in plant metabolic processes and defense responses. A few functions of plant CXE and MES genes have been identified but very little information is available about the role of most members. We made a comprehensive study of this gene family in a commercially important species, peach (Prunus persica L. Batsch). A total of 33 peach CXE genes and 18 MES genes were identified and shown to be distributed unevenly between the chromosomes. Based on phylogenetic analysis, CXEs and MESs clustered into two different branches. Comparison of the positions of intron and differences in motifs revealed the evolutionary relationships between CXE and MES genes. RNA-seq revealed differential expression patterns of CXE/MESs in peach flower, leaf, ripening fruit and in response to methyl jasmonate (MeJA) and ultraviolet-B (UV-B) treatment. Transcript levels of candidate genes were verified by real-time quantitative PCR (qPCR). Heterologous expression in Escherichia coli identified three CXEs that were involved in the hydrolysis of volatile esters in vitro. Furthermore, two recombinant MES proteins were identified that could hydrolyze MeJA and methyl salicylate (MeSA). Our results provide an important resource for the identification of functional CXE and MES genes involved in the catabolism of volatile esters, responses to biotic and abiotic stresses and activation of signaling molecules such as MeJA and MeSA.